Enhanced gas separation performance using mixed matrix membranes containing zeolite T and 6FDA-durene polyimide - Jusoh, N. (Elsevier B.V., 2017)
In the recent years, zeolite T has been demonstrated as a potential materials for adsorption, catalysis, pervaporation as well as gaseous separation processes. However, the reported literature on the application of zeolite T as inorganic filler for the fabrication of mixed matrix membranes (MMMs) in CO2/CH4separation is not available. Therefore, in the present work, different loadings of zeolite T particles are embedded in 6FDA-durene polyimide. The morphology and structural properties of the resultant membranes were investigated using different analytical tools and the performance of the membranes in CO2and CH4gases separation were tested. The results showed that CO2permeability of 843.6 Barrer and CO2/CH4ideal selectivity of 19.1 were obtained using 1 wt loaded zeolite T/6FDA-durene MMM, which were 80 and 172 higher than the CO2permeability and CO2/CH4ideal selectivity attained using pristine 6FDA-durene. Besides, the membrane showed improvement in CO2plasticization resistant up to 20 bar as compared to pristine 6FDA-durene membrane, which showed only 5 bar. Overall, zeolite T/6FDA-durene mixed matrix membranes fabricated in this work exhibited significant enhancement in CO2/CH4separation, which makes them an attractive candidate for industrial gas separation especially for natural gas purification. © 2016 Elsevier B.V.